(untitled) (International Journal of Engineering and Computer Science, 2017)
Energy is a key factor in the development of any country. The energy needs are increasing day by day. Both for economical and environmental reasons, efficient use of the electrical energy is the need of hour. In our project, we developed one circuit, which will control the utilization of electrical energy in the economical way, especially in the case of energy saving and power management services. An RFID (Radio Frequency Identification) tag consist of a small integrated circuit attached to a small antenna, capable of transmitting a unique serial number a distance of several meters to reading device in response to a query. This RFID tags are passive, these are battery less and obtain the power necessary to operate form the query signal itself. The main heart of the circuit is microcontroller chip, interfaced with different sensing circuit. In our project the energy saving is achieved in RFID based automatic electricity control using embedded technology. This tag has used to access the secured areas. User can display the particular RFID tag to this RFID reader it read this serial number and it also check with its internal serial number when this card serial number is matched it automatically open this door. Then it automatically turn on the special devices AC and light and fan when this person enter the this RFID tag against to this RFID reader then it automatically close the locker and turn off the special devices. Otherwise this card serial number is not matched then it does not allowed this secured room. When the manager has enter the RFID tag into this reader then it automatically turn on this manager special electrical appliance like AC and water heater etc. in this same manner when this employ has come to enter this room enter the tag into the RFID reader then it allow to turn on the person allowed electrical devices like Fan, and TV also. When this corresponding person leaves that particular office then it automatically switches of those particular special devices. So this projects achieved energy saving and avoid the miss usage of electrical appliances.